PENGEMBANGAN KEBAYA KONTEMPORER YOGYAKARTA DALAM SENTUHAN MOTIF BATIK GEBLEK RENTENG - Diah Indah Pratiwi; Hadjar Pamadhi; Sri Wening (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2022)
The study aims to make an effort to develop on an item of clothing in order to preserve cultural preservation and make a fashion that is acceptable to society today. The study picked up a study topic based on a traditional kebaya costume developed and modified to a contemporary kebaya with a traditional batik “geblek renteng”. The study focused on the development of kebaya jogja's clothing to contemporary kebaya, so the study is conducted with research and development (r&d). The research development model was the borg and gall. The development stage is done with a step that is 1) doing early research, 2) developing early products, 3) expert validation and revision, 4) small-scale field trials and 5) large-scale field trials and the final product. The findings of this study gave insight into the creation of traditional kebaya fashion modifications yogyakarta to a contemporary kebaya with a batik touch. Moreover, as a new motivation for valuing the culture and preserving it with new innovations.